NIMG-50. INITIAL EXPERIENCE: DETECTION OF ABERRANT HYPERPOLARIZED [1-13C]PYRUVATE METABOLISM IN PATIENTS WITH GBM PRIOR TO RESECTION. (9th November 2020) - Autry, Adam; Gordon, Jeremy; LaFontaine, Marisa; Chen, Hsin-Yu; Villanueva-Meyer, Javier; Chang, Susan; Clarke, Jennifer; Xu, Duan; Lupo, Janine; Larson, Peder; Vigneron, Daniel; Li, Yan
Abstract: INTRODUCTION: Detecting radiological response or resistance to treatment in patients with GBM is difficult with conventional MRI. In response to this challenge, hyperpolarized carbon-13 (HP- 13 C) MRI techniques were developed to probe real-time [1- 13 C]pyruvate metabolism. METHODS: Dynamic HP- 13 C MRI was acquired pre-operatively from 6 patientswith recurrent GBM following intravenous injection of HP [1- 13 C]pyruvate. Five were confirmed with tumor progression and one had treatment effects without progression. Frequency-selective echo-planar imaging (8 slices, 3s temporal resolution, 3.38 cm 3 spatial resolution, 60s acquisition) captured [1- 13 C]pyruvate metabolism to [1- 13 C]lactate and [1- 13 C]bicarbonate in the brain. Proton imaging included 3-D FLAIR, T1-weighted post-Gd IRSPGR, and spectroscopy. Carbon-13 voxels with non-enhancing lesion (NEL) or contrast-enhancing lesion (CEL) were identified for subsequent analysis. Temporally-summed HP- 13 C metabolite data within the CEL and NEL were evaluated using the pyruvate-to-lactate ratio; a modified ratio that takes into account vascular contributions of pyruvate; and parameter percentile ranks over the entire brain. Proton spectroscopy data were processed to obtain choline-to-NAA index (CNI) maps, which provide z-scores of relative tissue abnormality. RESULTS: All of the anatomic lesions displayed abnormal CNI with maximum values of 3.22-6.35. The 5 patients with CEL lesions demonstrated 87 th – 98 th percentile levels of pyruvate in the brain; and 95 th -100 th percentile levels of lactate in 4 progressed patients and 60 th percentile in the patient presenting with treatment effects. For the patient with an exclusively non-enhancing lesion, percentile levels of pyruvate and lactate were 66 th and 88 th in the brain, respectively. The mean+/-SD percentile of the lactate-to-pyruvate and modified ratios were 75+/-22, 86+/-23 and 60+/-3, 71+/-12 in the progressed and non-progressed patients, respectively. CONCLUSION: These data importantly demonstrate aberrant [1- 13 C]pyruvate metabolism in patients with GBM in both contrast-enhancing and non-enhancing lesions. Ongoing studies will further characterize the utility of HP imaging markers.